1995
DOI: 10.3109/02699209508985336
|View full text |Cite
|
Sign up to set email alerts
|

Teaching voiced velar stops to profoundly deaf children, using EPG—two case studies

Abstract: Older deaf children who have had amplification and auditory training from an early age to promote maximal use of residual hearing, can still frequently present with unintelligible speech. They not only require access to new speech-teaching techniques, but more importantly, carefully planned, realistic therapy goals. This pilot study explores the use of EPG in teaching two profoundly deaf 10-year-olds how to articulate initial voiced velar stops in familiar phrases. Whereas previous traditional therapy methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…(Crawford 1995;Parsloe 1998), however there are no similar studies for cochlear implant users. The purpose of this single case study is to explore the technique of EPG as a therapeutic intervention to treat voiceless velar stop consonant sound production in a deaf child cochlear implant user.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(Crawford 1995;Parsloe 1998), however there are no similar studies for cochlear implant users. The purpose of this single case study is to explore the technique of EPG as a therapeutic intervention to treat voiceless velar stop consonant sound production in a deaf child cochlear implant user.…”
mentioning
confidence: 99%
“…EPG has been used successfully to treat disorders ranging from dyspraxia (Hardcastle & Edwards 1992), dysarthria (Wood & Hardcastle 1999), cleft palate (Gibbon et al 2001;Whitehill, Stokes & Man, 1996), glossectomy (Fletcher 1988) and dysfluency (Wood 1993; to speech problems related to deafness (Fletcher & Hasegawa 1983;Dagenais & CritzCrosby 1991;Fletcher, Dagenais, & Critz-Crozby 1991a;Dagenais, Critz-Crozby, Fletcher & McCutcheon 1994;Crawford 1995;Parsloe 1998). However, no research to date has been based on children who have cochlear implants.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence in the literature that EPG therapy can affect change in speech production skills more quickly than traditional therapy (Bernhardt et al, 2003;Dagenais et al, 1994;Fletcher et al, 1991;Parsloe, 1998). There is also some evidence that production skills can be maintained in the short-term (Crawford, 1995;Dagenais et al, 1994;Pantelemidou et al, 2003). However, few longitudinal studies have been carried out to investigate the impact of phoneme-specific changes on intelligibility in connected speech or the longterm maintenance of skills.…”
Section: Introductionmentioning
confidence: 99%
“…M requested further therapy and EPG therapy was offered as an alternative approach. Crawford (1995) showed that alveolar plosives could be taught to two profoundly deaf children using EPG, in the absence of the ability to perceive the target contrast.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation